High-Intensity Interval Exercise versus Focused Ultrasound on Insulin Resistance in Diabetic Female with Abdominal Obesity - Eraky, Zeezy S.; Abd-Elrahman, Noha Ahmed Fouad; Elshinnawy, Ahmed M.; Elmasry, Haitham M.; Ali, Zeinab A.; El-Readi, Mahmoud Zaki; Ragab, Reem Hassan; Farahat MD, Heba Elmetwally Abdallah; Rashed, Shymaa E.; Ahmed Roshdy, Shimaa Hussien (International Journal of Aquatic Research and Environmental Studies, 2026)
Background: In women with type 2 diabetes mellitus (T2DM), abdominal obesity significantly increases insulin resistance. Focused ultrasound (FUS) decreases localized fat while high-intensity interval training (HIIT) enhances metabolic function. It’s yet uncertain how effective they are metabolically. Objective: To compare how HIIT and FUS affect insulin resistance and abdominal obesity in women with type 2 diabetes. Methods: For 16 weeks, thirty women with T2DM and abdominal obesity were randomized to either FUS + intermittent fasting (n = 15) or HIIT plus intermittent fasting (n = 15). Glycated hemoglobin (HbA1c) and the homeostasis model assessment of insulin resistance (HOMA-IR) were the main results. Waist circumference and body mass index (BMI) were secondary outcomes. To evaluate differences both within and between groups, a mixed-design MANOVA was employed. Results: Waist circumference and BMI were significantly lower in both groups (p<0.05). Only the HIIT group, however, demonstrated substantial reductions in HOMA-IR (−52.2%) and HbA1c (−27.5%) (p<0.001). Post intervention comparisons showed that the HIIT group had considerably lower HbA1c and HOMA-IR values than the FUS group (p<0.001), whereas the FUS group had larger waist circumference reductions (p<0.001). Conclusions: Despite comparable decreases in anthropometric measurements, HIIT produced greater improvements in insulin resistance and glycemic management than FUS. These results confirm that structured high-intensity exercise is the recommended non-pharmacological intervention for enhancing metabolic health in women with abdominal obesity and type 2 diabetes.